Modafinil for multiple sclerosis fatigue: does it work? - Littleton, E; Hobart, J; Palace, J (2010)
UNLABELLED: Modafinil is sometimes used in the clinical setting for treating multiple sclerosis (MS) fatigue, despite conflicting and disappointing results from clinical trials. OBJECTIVE: We audited the patient perceived effectiveness of modafinil when used in clinical practice in a carefully selected group of patients with typical MS fatigue. METHODS: All MS patients commenced on modafinil for fatigue in the Oxford MS clinic were identified retrospectively, and the patient perceived benefit, side effects and decision on continuation of therapy at 1 month was obtained from the medical notes. Additionally all patients were subsequently interviewed, up to 5 years after treatment initiation. RESULTS: Surprisingly, 69% patients with fatigue also suffered excessive daytime sleepiness, and this subgroup found modafinil more beneficial. There was a better response against excessive daytime sleepiness than fatigue. The benefit against fatigue or sleepiness was generally sustained (median 1 year). CONCLUSION: This suggests that modafinil may be useful, particularly when MS fatigue is associated with sleepiness. The relationship between fatigue and excessive daytime sleepiness is poorly understood and needs to be better defined before appropriate measures of the most clinically relevant outcomes can be selected for clinical trials. Outcome measures used in previous clinical trials have not properly evaluated the effects of modafinil.